Comparing the quality of life in adults who stutter with their normal counterparts - Banafsheh Mansuri; Mohammad Rahim Shahbodaghi; Seyed Abolfazl Tohidast; Mohammad Kamali (Vesnu Publications, 2013)
Introduction: Stuttering is a communication disorder that, in addition to speech fluency, can affect all aspects of personal life. Through numerous researches and also from the experiences of People Who Stutter (PWS), it is now evident that stuttering can cause an over all sense of life dissatisfaction. The aim of this study was to compare the quality of life in adults with stuttering versus their normal counterparts using the brief version of World Health Organization Quality Of Life Questionnaire. Materials and Methods: 25 adults with stuttering and 25 adults without stuttering, who were matched for age, sex and education level, participated in this cross-sectional analytic study. Tocollect data, World Health Organization Quality of Life Questionnaire was used. Independent sample t test was conducted for the statistical analysis of the data. Results: The results of data analysis showed that, except for social relationships domain, the difference between the two groups regarding total scores of quality of life, physical health, mental health and environmental health were statistically significant. Conclusion: The results of the present study showed that people who stutter have lower quality of life based on WHOQOL-BREF questionnaire. Thus, it is better to pay appropriate attention to in the quality of life of people who stutter during the evaluation and treatment processes rather than attending solely to speech fluency needs. Keywords: Quality of life, Stuttering, Adult persons